A Closer Look at Five Components of Speaking Performance in Indonesian EFL Students - Ilham, Moh.; Nurwati, Andi; Helingo, Adimawati (Innovative: Journal Of Social Science Research, 2024)
Recognize that speaking is an essential ability for effective communication. This study investigates at the five major components of speaking performance in English as a Foreign Language (EFL) students. Specifically, to examine the levels of grammar, pronunciation, vocabulary, fluency, and comprehension among EFL learners. The study uses qualitative descriptive research to provide a thorough grasp of students' speaking abilities. The data show that pronunciation is the strongest component, which can be linked to students' regular exposure to English through music, whereas vocabulary is the lowest, affecting overall fluency and comprehension. Conclusion: Pronunciation and comprehension are generally well developed, but vocabulary limitations considerably impair speaking performance. This study suggests introducing vocabulary-building strategies and interactive speaking activities into the curriculum. Also, establishing an immersive English-speaking atmosphere.